Effect of increasing dietary calcium through supplements and dairy food on body weight and body composition: a meta-analysis of randomised controlled trials. Issue 7 (3rd August 2015) - Booth, Alison O.; Huggins, Catherine E.; Wattanapenpaiboon, Naiyana; Nowson, Caryl A.
Abstract : This meta-analysis of randomised controlled trials assessed the effect of Ca on body weight and body composition through supplementation or increasing dairy food intake. Forty-one studies met the inclusion criteria (including fifty-one trial arms; thirty-one with dairy foods ( n 2091), twenty with Ca supplements ( n 2711). Ca intake was approximately 900 mg/d higher in the supplement groups compared with control. In the dairy group, Ca intake was approximately 1300 mg/d. Ca supplementation did not significantly affect body weight (mean change ( − 0·17, 95 % CI − 0·70, 0·37) kg) or body fat (mean change ( − 0·19, 95 % CI − 0·51, 0·13) kg) compared to control. Similarly, increased dairy food intake did not affect body weight ( − 0·06, 95 % CI − 0·54, 0·43) kg or body fat change ( − 0·36, 95 % CI − 0·80, 0·09) kg compared to control. Sub-analyses revealed that dairy supplementation resulted in no change in body weight (nineteen studies, n 1010) ( − 0·32, 95 % CI − 0·93, 0·30 kg, P = 0·31), but a greater reduction in body fat (thirteen studies, n 564) ( − 0·96, 95 % CI − 1·46, − 0·46 kg, P < 0·001) in the presence of energy restriction over a mean of 4 months compared to control. Increasing dietary Ca intake by 900 mg/d as supplements or increasing dairy intake to approximately 3 servings daily (approximately 1300 mg of Ca/d) is not an effective weight reduction strategy in adults. There is, however, an indication that approximately 3 servings of dairy may facilitate fat loss on weight reduction diets in the short term.